British Nuclear Energy Society one day seminar on the advances in nuclear safety Wednesday 7 July 1999 at the Conference Centre, British Energy plc, Barnwood, Gloucester, GL4 3RS. (British Energy plc, 1999)
These proceedings from a 1999 conference on nuclear safety cover such topics as the safety of fusion power, a new approach to preparing safety cases for existing nuclear plants, Ignalina NPP safety and licensing, managing safety at Dounreay for the future, and a seismic periodic safety review of Oldbury Power Station.